P026 One ward. one pharmacist. one bleep – a review of the women's and children's clinical pharmacy service. Issue 7 (19th June 2019) - Lo, Alice
Abstract : Background: The women's and children's pharmacy service provides morning visits to all paediatric, neonatal and gynaecology wards with a link bleep held by the band 6 pharmacist for afternoon requests. Recent feedback from band 6 rotational pharmacists that the volume of calls to their bleep after the morning ward pharmacist visits was high causing a lot of pressure and stress. With no major change in bed activity it was important to find the causes of the increased workload and solutions to any other issues to address the poor feedback. Aim: Review of the clinical link service to women's and children's services Methods: The paediatric team was briefed on the aim of the focus groups and an open and non-judgemental session was carried out to draw out the root causes and identify solutions to improve the women's and children's clinical pharmacy service. The team was divided into two groups of mixed seniority to initially discuss the problems before regrouping to theme the problems and then repeating to identify solutions to the problems. Result: Using fishbone analysis the following themes were identified to be problems: lack of continuity of specialist knowledge, women's wards, education and training, dispensary and information technology (IT). The solutions were then placed into an action priority matrix and assigned to various members of the team to carry out. Specialist knowledge: Lack of continuity of the ward pharmacist's in-depth knowledge of patients was identified as a heavy burden for junior pharmacists. They had to clinically screen new medicines or validate take home prescriptions (TTAs) of patients they didn't know including complicated cystic fibrosis, gastroenterology and oncology patients. A consensus solution was achieved by the team for ward pharmacists to be responsible for their patients throughout the day. The link pharmacist would cover for meetings and leave. New bleeps were obtained for all paediatric wards to have a dedicated bleep through the day. All wards were informed of the new system and bleep numbers. An audit is currently being carried out to determine how this affects the link bleep volumes as well as senior pharmacist time due to the extra workload and distance between the wards and the clinical office. Women's wards: Communication to the women's wards was recirculated to remind them of the link pharmacy service. A restructure of the team in October will give an additional band 6 pharmacist in place of two 0.33WTE equivalent band 7 pharmacists. This should provide wards with a pharmacist who is available after the morning visit. The link bleep will also be divided between the 2 band 6 pharmacists for women's and paediatric wards. Education and training: Senior pharmacists share their knowledge in team continuing professional development meetings but there is less one to one teaching. The junior pharmacists now receive teaching from specialist pharmacist ward visits including women's wards. Dispensary and IT: These are being reviewed by the pharmacy department. Conclusion: One week post implementation the workload to the band 6 has reduced and the impact to senior pharmacists is being reviewed. Reference: NHS Wales University Health Board. Change management toolkit 2012. Available at: www.wales.nhs.uk/bcupinnacle/opendoc/230961 Links to an external site.